2010
DOI: 10.1152/ajprenal.00016.2010
|View full text |Cite
|
Sign up to set email alerts
|

P2X1receptor blockade inhibits whole kidney autoregulation of renal blood flow in vivo

Abstract: In vitro experiments demonstrate that P2X(1) receptor activation is important for normal afferent arteriolar autoregulatory behavior, but direct in vivo evidence for this relationship occurring in the whole kidney is unavailable. Experiments were performed to test the hypothesis that P2X(1) receptors are important for autoregulation of whole kidney blood flow. Renal blood flow (RBF) was measured in anesthetized male Sprague-Dawley rats before and during P2 receptor blockade with PPADS, P2X(1) receptor blockade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 43 publications
3
36
3
1
Order By: Relevance
“…The central role of the P2 system is further suggested by the fact that pressure-induced reductions in afferent arteriole diameter are abolished in P2X1-deficient mice [152]. Pharmacological [272] or pathological [119] manoeuvres that impair P2X1 receptor signalling will also blunt whole kidney autoregulation of blood flow, both in vivo and in vitro. Finally, mice with a targeted deletion of the ectonucleotidase NTPDase1 exhibit enhanced pressureinduced vasoconstriction in the mesenteric artery [183].…”
Section: Myogenic Responses To Altered Perfusion Pressurementioning
confidence: 99%
“…The central role of the P2 system is further suggested by the fact that pressure-induced reductions in afferent arteriole diameter are abolished in P2X1-deficient mice [152]. Pharmacological [272] or pathological [119] manoeuvres that impair P2X1 receptor signalling will also blunt whole kidney autoregulation of blood flow, both in vivo and in vitro. Finally, mice with a targeted deletion of the ectonucleotidase NTPDase1 exhibit enhanced pressureinduced vasoconstriction in the mesenteric artery [183].…”
Section: Myogenic Responses To Altered Perfusion Pressurementioning
confidence: 99%
“…It is now established that P2X receptors, ligand-gated Ca 2+ -permeable cation channels expressed in the plasma membrane of vascular smooth muscle cells (VSMC), are responsible for vasoconstrictor responses induced by neuronal released ATP. In muscular arteries, it is proposed that activation of P2X receptors leads to membrane depolarisation, followed by an increase in intracellular Ca 2+ concentration ([Ca 2+ ] i ) and vasoconstriction, which evokes a rise in blood pressure [17,24]. Therefore P2X receptors may represent an important therapeutic target for treatment of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…However, we cannot rule out that, in the presence of NO blockade the effect of endogenous vasoconstrictor mediators could be enhanced and alter renal function. It is recognized that the renal vasoconstriction observed in the Sham rats with PPADS (Franco et al 2011) was not observed by Tanaka el al (Takenaka et al, 2008) or Osmond and Inscho (Osmond & Inscho, 2010); these authors used an intravenous bolus, each 20 min with a lower dose than ours. Under those conditions, lower concentrations of PPADS possible reach the kidney; however the dose used in those studies (Osmond & Inscho, 2010) were sufficient to block P2 receptors as evidenced by the blockade of the vasoconstrictor response to ,methylene ATP; thus an explanation for the divergent effects of PPADS in Sham rats remains to be elucidated.…”
Section: Wwwintechopencommentioning
confidence: 53%